The Carbon Switch at the Level of Pyruvate and Phosphoenolpyruvate in Sulfolobus solfataricus P2 - Haferkamp, Patrick; Tjaden, Britta; Shen, Lu; Bräsen, Christopher; Kouril, Theresa; Siebers, Bettina (Frontiers in Microbiology, 2019)
Sulfolobus solfataricus P2 grows on different carbohydrates as well as alcohols, peptides and amino acids. Carbohydrates such as D-glucose or D-galactose are degraded via the modified, branched Entner-Doudoroff (ED) pathway whereas growth on peptides requires the Embden-Meyerhof-Parnas (EMP) pathway for gluconeogenesis. As for most hyperthermophilic Archaea an important control point is established at the level of triosephophate conversion, however, the regulation at the level of pyruvate/phosphoenolpyruvate conversion was not tackled so far. Here we describe the cloning, expression, purification and characterization of the pyruvate kinase (PK, SSO0981) and the phosphoenolpyruvate synthetase (PEPS, SSO0883) of Sul. solfataricus. The PK showed only catabolic activity (catalytic efficiency (PEP): 627.95 mM-1s-1, 70°C) with phosphoenolpyruvate as substrate and ADP as phosphate acceptor and was allosterically inhibited by ATP and isocitrate (Ki 0.8 mM). The PEPS was only active in the gluconeogenic direction (catalytic efficiency (pyruvate): 1.04 mM-1s-1, 70°C) and showed some allosteric inhibition by AMP and α-ketoglutarate. The gene SSO2829 annotated as PEPS/pyruvate:phosphate dikinase (PPDK) revealed neither PEPS nor PPDK activity. Our studies suggest that the energy charge of the cell as well as the availability of building blocks in the citric acid cycle and the carbon/nitrogen balance plays a major role in the Sul. solfataricus carbon switch. The comparison of regulatory features of well-studied hyperthermophilic Archaea reveals a close link and sophisticated coordination between the respective sugar kinases and the kinetic and regulatory properties of the enzymes at the level of PEP-pyruvate conversion.